The role of school governing bodies on learner performance in selected schools in the Sekgosese East Circuit of Limpopo - Selamolela, Ngwako Fannie (University of Limpopo, 2019)
School Governing Bodies in South Africa were established in 1997 in line with the new democratic dispensation following the enactment of the South African Schools Act (SASA).The purpose of SGBs was to give decision making powers to local communities. It was intended to be a break away from the apartheid principle of centralised decision-making. Stakeholders were given the opportunity to partake in decision-making that affected education in the local community.This study focuses on the role of school governing bodies in rural areas. To obtain rich data, the researcher used the mixed methods approach. Both quantitative and qualitative data were collected. Qualitative data was collected through the use of a questionnaires administered to sixty(60) respondents. Further qualitative data was obtained through both semi-structured interviews and document analysis. Participants in the semi-structured interview were principals and SGB chairpersons or deputy chairpersons. The semi-structured interview involved five(05) principals, four (04) SGB chairpersons and one(01) SGB deputy chairperson. In the opinion of the researcher, sample was representative. Analysis of data obtained revealed several findings. One of the findings is that SGBs still face challenges in the performance of their roles and responsibilities. Training programmes offered by the Department of Education are inadequate. Parental involvement poses a challenge to most SGBs in that most parents are unemployed and view participation in the SGB as a waste of time. Recommendations include intensifying training programmes for members of School Governing Bodies. The content of training programmes should be suited to the developmental needs of SGB members. The Department of Education, at national level, should also consider introducing a stipend for SGB members. Recommendations for further research are made with regard to strengthening parental involvement in School Governing Bodies
Thesis( MPA.) -- University of Limpopo, 2019
Keywords: School governing body; Education; Discipline; School performance; Academic achievement; School discipline -- South Africa -- Limpopo; School management and organization -- South Africa -- Limpopo